Implementation of lean tools and techniques in an ethical papers production industry - Kukhan S; Manickam Bhuvanesh Kumar (Jurnal Sistem dan Manajemen Industri, 2021)
Lean manufacturing (LM) is established as a best practice to improve the performance of manufacturing industries. Not all the manufacturing industries realize the benefits of LM practices specifically continuous process industries. The present research work is intended to study the advantages of implementing LM practices in an ethical paper industry which is a continuous production industry. Presently, the industry suffers with the problems such as lack of productivity, raw material wastes, underutilized resources, and lack of standard practices in the production. Gemba technique is adapted to record the information related to the present manufacturing environment. Based on the current state analysis, the feasible lean tools are selected and implemented such as 5S, Kaizen, and Total Productive Maintenance (TPM). The improvements have been noted as reduced tool change over time, reduced material wastes, effective utilization of resources and provide safety guidelines to workers and operations. The implications of these improvements increased the productivity also.